Toxicity of nanomaterials : environmental and healthcare applications - Pillai, Suresh C.; Lang, Yvonne (Boca Raton : CRC Press, 2019)
This comprehensive book, edited by two leading experts in nanotechnology and bioengineering with contributions from a global team of specialists, provides a detailed overview of the environmental and health impacts associated with the toxicology of nanomaterials. Special attention is given to nanomaterial toxicity during synthesis, production and application, and chapters throughout are focused on key areas that are important for future research and development of nanomaterials. This book will be of interest to advanced students studying biomedical engineering and materials science, PhD researchers, post-docs and academics working in the area of nanotechnology, medicine, manufacturing and regulatory bodies. Features: Collates and critically evaluates various aspects of the toxicology of nanomaterials in one comprehensive text Discusses the various effects of nanocrystals including the morphologies on cytotoxicity, in addition to the environmental and cytotoxicity risks of graphene and 2D nanomaterials Explores practical methods of detection and quantification, with applications in the environmental and healthcare fields
OCLC-licensed vendor bibliographic record.
Keywords: Nanostructured materials -- Toxicology; MEDICAL / Pharmacology; SCIENCE / Solid State Physics; TECHNOLOGY / Nanotechnology